The tissue proteome of dorsal root ganglia in Friedreich ataxia. (May 2021) - Koeppen, AH; Travis, AM; Qian, J; Mazurkiewicz, JE; Gelman, BB; Pelech, S; Sutter, C
Abstract : Dorsal root ganglia (DRG) at all levels of the spinal cord are a prominent target of Friedreich ataxia (FA). The lesions include hypoplasia of neurons, proliferation of satellite cells, infiltration by IBA- 1-reactive monocytes, and formation of residual nodules. Paucity and smallness of DRG neurons account for the lack of large myelinated axons in dorsal roots and sensory peripheral nerves. The lack of myelin in dorsal roots can be attributed to low levels of neuregulin 1 type III (NRG1[III]). Lysates of 13 DRG of genetically confirmed FA patients were analyzed by antibody microarray with 878 different validated antibodies that target structural and signaling proteins, and by Western blots. KIT and mTOR, two proteins involved in cellular proliferation, were significantly upregulated in the DRG of FA. KIT is a transmembrane receptor that dimerizes when it binds two molecules of stem cell factor (SCF) in its extracellular domain and becomes activated as protein tyrosine kinase. Immunohistochemistry with anti-KIT generated reaction product in satellite cells of normal DRG and prominent labeling of these cells in FA that co-localized with SCF on double- label immunofluorescence; SCF was present in S100-positive satellite cells rather than monocytes. Immunohistochemical reaction product of mTOR and other mTOR complex proteins, such as hamartin (TSC1), tuberin (TSC2), raptor (mTOR complex 1) and rictor (mTOR complex 2) was also present in satellite cells of normal DRG and DRG of FA. Antibodies to two downstream proteins that are considered to be indicators of mTOR activity, P70 S6K and 4E-binding protein 1, revealed no reaction product in DRG of FA. TSC1, TSC2, and mTOR are best known from their roles in tuberous sclerosis, but expression of these proteins, and KIT, in DRG may contribute to signaling cascades underlying the proliferation of satellite cells in FA. LEARNING OBJECTIVES: This presentation will enable the learner to: 1. Discuss cellular proliferation in the pathogenesis of the DRG lesion in Friedreich ataxia CONFLICT OF INTEREST: AHK is a consultant to PTC Therapeutics of South Plainfield, NJ USA. SP and CS are majority owners of Kinexus.